Comparison of Effectiveness Test Result of Several Disinfectants on the Growth of Escherichia Coli - Sari, Widia; Astari, Chitra; Hurria, Hurria (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Disinfectants are known as substances  that can kill pathogens in the environment. Disinfectants are used in hospitals, homes and often used to inhibit the proliferation of harmful bacteria and germs. The large number of disinfectants circulating in the community today makes people less aware of and know which disinfectant is good and has the best effectiveness of killing bacteria. Therefore testing the efficacy of several active disinfectant substances was carried out to show the most effective disinfectant to use, thus provided information and comprehension to the public about the most effective disinfectants to kill bacteria that could be used to inhibit the proliferation of harmful bacteria and germs. This research has never been done before. The method used was the inoculating Escherichia Coli bacteria on sodium media to solidify a continuous spread plate. The disc paper dipped in a disinfectant solution (70% alcohol, 5% Lysol, iodine, and 5% hypochlorite) was placed on the Nutrient Agar media, incubated for 48 hours at 370C. The measurement was taken of the diameter of the formed inhibition zone. Of the four treatments with four active disinfectant substances used, the one that gives the most antimicrobial effect is the 5% hypochlorite active substance; the extent of the inhibition zone obtained indicates this.